A value-based approach to prostate cancer image-guidance in a regional radiation therapy centre: a cost-minimisation analysis. (December 2022) - Robards, Shannon; Brown, Amy; Pain, Tilley; Patel, Deepti; Tan, Alex; Carter, Hannah
Highlights: Same day prostate fiducial insertion and CT simulation did not compromise outcomes. Same day insertion has benefits for both the health service and the patients. Health savings of AU$361 accrues per patient. There are increased efficiencies including appointment availability. Patient benefits include: reduced travel, increased access and affordability. Abstract: Background and objectives: Usual practice for the insertion of prostate fiducial markers involves at least one week delay between insertion and simulation. An evidence-based practice change was implemented whereby fiducial marker insertion occurred on the same day as radiotherapy simulation. The aim of this study was to quantify the health service costs and clinical outcomes associated with this practice change. Methods: A cost-minimisation analysis was undertaken from the perspective of the local health service. A retrospective chart audit was conducted to collect data on 149 patients in the pre-implementation cohort and 138 patients in the post-implementation cohort. Associated costs with insertion and simulation were calculated and compared across the two cohorts; this included subsided travel costs for rural and remote patients. Fiducial marker positions on planning CT and first treatment CBCT were measured for all patients as the surrogate clinical outcome measure for oedema. Results: The health service saved an average of AU$ 361 (CI $311 – $412) per patient after the practice change. There was no significant difference in fiducial marker position pre- and post- implementation (p < 0.05). Conclusion: The practice change to perform insertion and radiotherapy simulation on the same day resulted in substantial savings to the health system, without compromising clinical outcomes. The decrease in number of required patient attendances is of real consequence to rural and remote populations. The practice change increases both the value and accessibility of best-practice health care to those most at risk of missing out.